From paper to electronic dictionaries: Evolving dictionary skills - Lew, Robert (Airlangga University Press, 2013)
Successful dictionary use depends on two factors: (1) user-friendliness of dictionaries and (2) good dictionary reference skills of their users. As the world moves from paper to electronic dictionaries, we need to realize that the skills needed to use modern digital dictionaries are not necessarily identical to those for traditional print dictionaries. Some print dictionary skills are transferable to the context of digital products, whereas some other skills are no longer relevant, often because electronic dictionaries may now be able to do part of what used to be the user’s job (such as automatically reducing an inflected form to a citation form). On the other hand, using electronic dictionaries may require new types of reference skills, not known from paper dictionaries. The most salient group of new skills is related to searching for information, and may be subsumed under the more general concept of digital literacy. In the present contribution I consider which paper dictionary skills are still relevant for digital dictionaries, which are obso-lete, and what types of skills are new to electronic dictionaries.
Keywords: electronic dictionary; digital dictionary; dictionary skills; reference skills; digital literacy; information literacy